Imaginative thinking skills of students-teachers in the Department of Mathematics / Colleges of Basic Education (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the current research is to identify the imaginative thinking skills of students_teachers in the Department of Mathematics / Faculties of Basic Education. The research community was limited to students-teachers in the Department of Mathematics in the Colleges of Basic Education, in the Iraqi universities (Al-Mustansiriya, Maysan, Diyala, Mosul, Tal Afar, Tikrit, Kufa) in the morning study for the academic year 2021-2022. The Mathematics Department of the universities (Al-Mustansiriya, Maysan, Diyala) with a total number of (440) male and female students. The two researchers prepared a measure of the imaginative thinking skills of the students-teachers in the Mathematics Department, and it consisted of ((30 paragraphs in its final form). From the stability of the scale using the internal consistency coefficient method (Alpha-Cronbach), the stability coefficient was (0.874).After applying the research tool to the sample, the scale was corrected and the data was sorted and analyzed statistically. And females in their possession of imaginative thinking skills.In the light of these results, the researchers reached a number of conclusions, recommendations and suggestions.Keywords: imaginative thinking skills, students-teachers.